2019
DOI: 10.1103/physrevapplied.12.024009
|View full text |Cite
|
Sign up to set email alerts
|

Competing Nonlinear Delocalization of Light for Laser Inscription Inside Silicon with a 2- µ m Picosecond Laser

Abstract: The metrology of laser-induced damage usually finds a single transition from 0% to 100% damage probability when progressively increasing the laser energy in experiments. We observe that picosecond pulses at 2-µm wavelength focused inside silicon provide a response that strongly deviates from this. Supported by nonlinear propagation simulations and energy flow analyses, we reveal an increased light delocalization for near critical power conditions. This leads to a nonmonotonic evolution of the peak delivered fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 21 publications
7
43
0
Order By: Relevance
“…The absence of any damage at short pulse duration is symbolized by the 'A' region covering even shorter pulse durations by combining this observation with previous reports [2,9,21]. With the range of pulse durations accessible with the designed stretcher, we expect modification comes into picture as observed in some other previous works [5,23]. Interestingly, our shortest accessible pulse duration of 4 ps (due to the minimum distance that can be set between gratings) leads to the same conclusion as for the femtosecond pulse irradiation.…”
Section: Energy Thresholds For Bulk Modificationsupporting
confidence: 85%
See 4 more Smart Citations
“…The absence of any damage at short pulse duration is symbolized by the 'A' region covering even shorter pulse durations by combining this observation with previous reports [2,9,21]. With the range of pulse durations accessible with the designed stretcher, we expect modification comes into picture as observed in some other previous works [5,23]. Interestingly, our shortest accessible pulse duration of 4 ps (due to the minimum distance that can be set between gratings) leads to the same conclusion as for the femtosecond pulse irradiation.…”
Section: Energy Thresholds For Bulk Modificationsupporting
confidence: 85%
“…While single shot modifications are hardly detectable, we found that 1000 shots are usually appropriate for the growth of the modifications and unambiguous detection. Applying the pulse sequences at 1 kHz repetition rate, we do not introduce any thermal accumulation effect to account in these experiments [5,23] and we only benefit from incubation in comparison from a single-shot study. For the investigations at different pulse durations, the maximum pulse energy impinging the Si target is 1.95 µJ (measured after the objective lens) corresponding to the maximum fluence of 86 J/cm 2 with theoretical beam diameter 1.22λ/NA 2.4 µm in air.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations